Dengue expansion in Africa—Not recognized or not happening? - Jaenisch, T; Junghanss, T; Wills, B; Brady, O; Eckerle, I; Farlow, A; Hay, S; McCall, P; Messina, J; Ofula, V; Sall, A; Sakuntabhai, A; et al. (Centers for Disease Control and Prevention (CDC), 2014)
An expert conference on Dengue in Africa was held in Accra, Ghana, in February 2013 to consider key questions regarding the possible expansion of dengue in Africa. Four key action points were highlighted to advance our understanding of the epidemiology of dengue in Africa. First, dengue diagnostic tools must be made more widely available in the healthcare setting in Africa. Second, representative data need to be collected across Africa to uncover the true burden of dengue. Third, established networks should collaborate to produce these types of data. Fourth, policy needs to be informed so the necessary steps can be taken to provide dengue vector control and health services.